2004
DOI: 10.1007/s00425-003-1168-3
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization and topology of �(1?4)galactosyltransferase that elongates �(1?4)galactan side chains in rhamnogalacturonan�I in potato

Abstract: The subcellular localization and topology of rhamnogalacturonan I (RG-I) beta(1-->4)galactosyltransferase(s) (beta[1-->4]GalTs) from potato ( Solanum tuberosum L.) were investigated. Using two-step discontinuous sucrose step gradients, galactosyltransferase (GalT) activity that synthesized 70%-methanol-insoluble products from UDP-[(14)C]Gal was detected in both the 0.5 M sucrose fraction and the 0.25/1.1 M sucrose interface. The former fraction contained mainly soluble proteins and the latter was enriched in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The subcellular localization of GALS1 was investigated by heterologous expression of a yellow fluorescent protein (YFP) fusion in Nicotiana benthamiana and confocal laser scanning microscopy. This analysis showed that GALS1 was targeted to Golgi vesicles, consistent with a role in pectin biosynthesis and the reported location of b-1,4-galactan synthase activity (Geshi et al, 2004) (Figure 4). GALS2 and GALS3 have previously been identified as putative Golgi proteins in a proteomic study of purified Golgi vesicles from Arabidopsis cell cultures (Parsons et al, 2012).…”
Section: Gals1 Is Located In the Golgi Apparatussupporting
confidence: 83%
“…The subcellular localization of GALS1 was investigated by heterologous expression of a yellow fluorescent protein (YFP) fusion in Nicotiana benthamiana and confocal laser scanning microscopy. This analysis showed that GALS1 was targeted to Golgi vesicles, consistent with a role in pectin biosynthesis and the reported location of b-1,4-galactan synthase activity (Geshi et al, 2004) (Figure 4). GALS2 and GALS3 have previously been identified as putative Golgi proteins in a proteomic study of purified Golgi vesicles from Arabidopsis cell cultures (Parsons et al, 2012).…”
Section: Gals1 Is Located In the Golgi Apparatussupporting
confidence: 83%
“…It has been known for a long time that noncellulosic polysaccharides are synthesized in the Golgi apparatus (Ray et al, 1969), and enzymes involved in the synthesis of the backbone of noncellulosic b-linked CW polysaccharides (e.g., the mannan synthases) have been shown to be Golgi localized, multimembranespanning enzymes (Dhugga et al, 2004;Liepman et al, 2005). Evidence pointing toward pectin also being synthesized in the Golgi has been reviewed by Staehelin and Moore (1995), and it has since then been substantiated by biochemical evidence that three enzymes involved in pectin biosynthesis are bound to the Golgi membrane with the active site facing the lumen (Goubet and Mohnen, 1999;Sterling et al, 2001;Geshi et al, 2004). It is therefore very likely that RG-II is also assembled in the Golgi vesicles, which is supported by the accumulation of RGXT1-EGFP and RGXT2-EGFP fusion proteins in an intracellular compartment that disintegrates upon treatment with BFA.…”
Section: Protein Structure and Subcellular Localizationmentioning
confidence: 99%
“…Different epitopes present in pectin have been detected in various compartments of the Golgi apparatus (Staehelin and Moore, 1995;Willats et al, 2001), and enzymes synthesizing pectin have been detected in Golgiderived vesicles (Goubet and Mohnen, 1999;Sterling et al, 2001;Geshi et al, 2004), indicating that pectin is indeed synthesized in the Golgi apparatus. Glycosyltransferases (GTs) located in the Golgi apparatus typically have a type II membrane protein structure consisting of a single N-terminal transmembrane domain (TMD), followed by a stem-like region of variable length and the C-terminal catalytic domain facing the lumen of the Golgi apparatus (Breton et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…More recent topology studies of such glycosyltransferases include the protection of enzyme activities from protease treatment by the Golgi membranes, for the -1, 4-galacturonosyltransferase involved in the biosynthesis of homogalacturonan (Sterling et al 2001), and the -1, 4-galactosyltransferase involved in the synthesis of -1, 4-galactan side chains in rhamnogalacturonan I (Geshi et al 2004). On the other hand, the maize mixed linkage (1-3), (1-4)--D-glucan synthase was found to be sensitive to pretreatments of Golgi membranes with proteinase K (Urbanowicz et al 2004).…”
Section: Introductionmentioning
confidence: 99%